Қазақстанда сценографияның шығу тегі мен дамуы (Journal of Philosophy, Culture and Political Science, 2018)
This article discussed in theoretical and methodological problem connecting with the new models and an attempt the hermeneutical and ontological status for category of «theater area» to others modern scene design of Kazakhstan. Also in the article of explaining of scene design is given an analysis as «text art».